Depression and Cancer (literature review) - A. N. Blinkov (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2020)
Current review describes the issues of prevalence, diagnosis, pathogenesis, implications, and psychosocial treatment of depression in oncology patients. The prevalence of emotional disorders in oncology patients is significantly higher while the prevalence of major depressive disorder is comparable to the numbers presented among general population. The depression can occur as a psychological reaction of personality in response to the diagnosis of cancer, due to specific neuro-immuno-endocrine mechanisms related to this stress factor, and can be developed in the course of biological changes, caused by the progressive malignant process and its chemotherapy treatment. Modern comprehensive psychosocial care programs for oncology patients with depression have been designed and consist of several modules. These therapeutic programs are applied in clinical practice and mostly delivered by nonprofessionals in the field of mental health.